2009
DOI: 10.1021/om800570r
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Water-Soluble Alkyl-bis(m-sulfonated-phenyl)- and Dialkyl-(m-sulfonated-phenyl)-phosphines and Their Evaluation in Rhodium-Catalyzed Hydrogenation of Maleic Acid in Water

Abstract: The combined application of 31P NMR and pH measurements during the tri-isooctylamine-assisted aqueous/organic separation and purification steps after the sulfonation of diphenyl-alkyl-phosphines (Ph2PR; R = Me, n-Bu) and phenyl-dialkyl-phosphines (PhPR2; R = Me, n-Bu) resulted in the preparation of water-soluble alkyl-bis(m-sulfonated-phenyl)- (C6H4-m-SO3Na)2PR; R = Me, n-Bu) and dialkyl-(m-sulfonated-phenyl)- (C6H4-m-SO3Na)PR2; R = Me, n-Bu) phosphines in the presence of less than 0.5% phosphine oxides. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In order to approach the activity of the trialkylphosphine modified system, the influence of the electron-donating watersoluble alkyl-bis(m-sulfonated-phenyl)-(L1, L2), dialkyl-(msulfonatedphenyl)phosphines (L5, L6), 36 and TPPTS on the hydrogenation of LA was investigated under 100 bar H 2 (Table 2, entries 1-5). It was clearly demonstrated that the catalytic activity could be considerably enhanced by the incorporation of one or two alkyl functional group(s) into the phosphorus ligands.…”
Section: Hydrogenation Of Levulinic Acid To γ-Valerolactonementioning
confidence: 99%
See 1 more Smart Citation
“…In order to approach the activity of the trialkylphosphine modified system, the influence of the electron-donating watersoluble alkyl-bis(m-sulfonated-phenyl)-(L1, L2), dialkyl-(msulfonatedphenyl)phosphines (L5, L6), 36 and TPPTS on the hydrogenation of LA was investigated under 100 bar H 2 (Table 2, entries 1-5). It was clearly demonstrated that the catalytic activity could be considerably enhanced by the incorporation of one or two alkyl functional group(s) into the phosphorus ligands.…”
Section: Hydrogenation Of Levulinic Acid To γ-Valerolactonementioning
confidence: 99%
“…To better understand the influence of the electronic and steric properties of the ligands on the hydrogenation, a series of sulfonated phosphines were tested for GVL production under 10 bar of H 2 and 140 °C (Table 2, entries 6-15). According to published methods 36 the novel sulfonated L3, L4, L7, L8, L9, and L10 have been prepared and characterized (Table 1). Although, the alkyl substituent increases the electron density of the phosphorus ligands, the comparison of the activity of mono-and dialkyl phosphine modified systems revealed higher activity of monoalkyl species for each pair.…”
Section: Hydrogenation Of Levulinic Acid To γ-Valerolactonementioning
confidence: 99%
“…TPPTS ((3,3 0 ,3 00 -phosphanetriyltris(benzenesulfonic acid) trisodium salt), P(C 6 H 4 -m-SO 3 Na) 3 ) 35 and BuP(C 6 H 4 -m-SO 3 Na) 2 (Bu-DPPDS) 36 ligands were prepared by published methods.…”
Section: Methodsmentioning
confidence: 99%
“…2) with different stereoelectronic properties have been used to evaluate their catalytic properties in the aqueous biphasic hydrogenation of aromatic hydrocarbons. Ligands 1-3 were synthesized according to the literature procedures [39][40][41][42]. In order to rationalize their catalytic behavior we characterized their stereoelectronic nature.…”
Section: Characterization Of the Phosphine Ligandsmentioning
confidence: 99%
“…Solvents were purified, dried and deoxygenated by standard methods . Sulfonated phosphines 1a-b, 2a-b, 2d and 3a-c were synthesized according to the literature procedures [39][40][41][42]. All other starting materials were purchased from Aldrich.…”
Section: General Experimental Detailsmentioning
confidence: 99%